On coding over the spatial-temporal diversity for reliable transmission scheme in low-duty-cycle WSN - Yu-bo YAN; Pan-long YANG; Lei ZHANG; Zheng-lun QIU; Shan-lin HONG (Tongxin xuebao)
A reliable data delivery scheme for low-duty-cycle wireless sensor networks(WSN)was proposed.Using this scheme,the unique spatial-temporal diversity in low-duty-cycle WSN was explored and exploited.Combining with coding schemes,the proposed scheme could achieve higher energy efficiency and lower delivery delay.The coding block allocation problem over multiple paths was formulated.As it was NP-hard,an approximate algorithm to tackle this difficulty was proposed.The impact of network parameters was further analyzed with experimental methods.Extensive simulations also show that,the coding over the spatial-temporal diversity scheme could achieve relatively reliable and low delay delivery with relatively less energy.